Liposomal delivery systems for anti-cancer analogues of vitamin E - Koudelka, Stepan; Turanek Knotigova, Pavlina; Masek, Josef; Prochazka, Lubomir; Lukac, Robert; Miller, Andrew D; Neuzil, Jiri; Turanek, Jaroslav (Journal of controlled release, 2015)
Pro-apoptotic analogues of vitamin E (VE) exert selective anti-cancer effect on various animal cancer models. Neither suitable formulation of α-tocopheryl succinate (α-TOS), representative semi-synthetic VE analogue ester, nor suitable formulations of the other VE analogues for clinical application have been reported yet. The major factor limiting the use of VE analogues is their low solubility in aqueous solvents. Due to the hydrophobic character of VE analogues, liposomes are predetermined as suitable delivery system. Liposomal formulation prevents undesirable side effects of the drug, enhances the drug biocompatibility, and improves the drug therapeutic index. Liposomal formulations of VE analogues especially of α-TOS and α-tocopheryl ether linked acetic acid (α-TEA) have been developed. The anti-cancer effect of these liposomal VE analogues has been successfully demonstrated in pre-clinical models in vivo. Present achievements in: (i) preparation of liposomal formulations of VE analogues, (ii) physico-chemical characterization of these developed systems and (iii) testing of their biological activity such as induction of apoptosis and evaluation of anti-cancer effect are discussed in this review.
Keywords: liposomy; lipidy; Liposomes; apoptóza; Analogues of vitamin E; Nanomedicine; alpha-Tocopherol; farmaceutická chemie; Liposome; lékové transportní systémy; Alpha-tocopheryl succinate; Antineoplastic Agents; Chemistry, Pharmaceutical; Lipids; Neoplasms; protinádorové látky; zvířata; Humans; nádory; Drug delivery systems; Drug targeting; Solubility; vitamin E; alfa-tokoferol; Drug Delivery Systems; Anti-cancer drugs; rozpustnost; Vitamin E; lidé; Apoptosis; Animals